Digital Printing: Beyond the Image Problem - Rundle, Jamie Martin (2007)
Abstract The printing industry has experienced cyclical change throughout its history. Since the advent of early hand-operated printing presses to the introduction of mechanical, high-volume technology the industry has evolved, for the most part, incrementally. Printing firms have capitalised on developments with various degrees of success.